The consequences of the statutory regulation of customary law: an examination of the South African customary law of succession and marriage - Osman, Fatima (PER/PELJ, 2019)
In pluralistic legal systems, the regulation of non-state law through statute carries the risks associated with codification; namely the ossification and distortion of law. This article examines the effects of statutory regulation on unwritten systems of law in the South African legal context. It argues that the constitutional recognition of customary law in South Africa has forced the state to legislate in this arena, the most notable enactments being the Recognition of Customary Marriages Act 120 of 1998 and the Reform of Customary Law of Succession and Regulation of Related Matters Act 11 of 2009. The enactments' attempt to align customary law with constitutional values have imported significant portions of the common law to regulate the customary law of marriage and succession. This has resulted in a distortion of customary law to reflect common law values and rules. Furthermore, it is argued that significant lacunae in the enactments have necessitated litigation and resulted in the judiciary playing a significant role in shaping customary law. Finally, despite the incorporation of living customary law into the enactments, the implementation thereof by courts and in practice has – and perhaps inevitably so – ossified and distorted portions of the law. Nonetheless, the article argues that legislation is critical to regulate customary law. It advocates that the shortcomings identified in the article are addressed to ensure a more accurate portrayal of customary law in legislation and the successful implementation thereof.
Keywords: South-Africa; Distortion; Customary law; Marriage; Succession; Official customary law; Living customary law